Phytochemical Characteristics and Antioxidant Activity of Liang Tea at Different pH During Storage - Yohana Sutiknyawati Kusuma Dewi (Gorontalo Agriculture Technology Journal, 2022)
Tea is a popular beverage consumed in Pontianak City, Indonesia. The ingredients of tea were consist of the leaves of D.chinensis, R.discolor, O.aristatus, P.amaryllifolius, heartwood of C.sappan and peels of A.vera with certain ratio. The study aims to find out the effect of storage time on phytochemical content and antioxidant activity of  liang tea with different pH. The liang tea was prepared by hot brewing of the tea ingredients for 6 minutes and let it cooled down. The pH of tea adjusted to 4, 5, 6 and 6,5 by adding citric acid buffer and stored in plastic container and leave it at room temperature. The observed parameters were pH, vitamin C content, Total Soluble Solid (TSS), total phenolic content, total flavonoid content and antioxidant activity by DPPH scavenging method. Each of mentioned parameters of tea were observed for 17 days, with 2 days interval measurement. The treatment was replicated five times. The results in averaged time showed that liang tea with pH 4 possess highest total phenolic content and TSS (13.04 ± 1.21 mgGAE/g dw and 2.40 ± 0.3oBrix respectively) and pH 5 liang tea possess highest vitamin C, total flavonoid content and antioxidant activity (5.49 ± 0.94 mg/100ml; 20.02 ± 2.12 mgQE/g dw and 40.38 ± 4.37 % respectively. Base on the result showed the optimum pH of liang tea during storage was ranged 4 to 5, which pH 4 liang tea possess highest total phenolic content and total dissolved solid and pH 5 liang tea possess highest vitamin C, total flavonoid content and antioxidant activity.